How Corporate Governance Determines a Company's Financial Performance and The Likelihood of Financial Distress - Wulansuci, Rohmah (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
This study aims to analyze the role of intellectual capital as a moderating variable on the influence of corporate governance on financial performance and governance on the possibility of financial distress. This study uses panel data regression to analyze 412 units of observation from 103 manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The results of the study show that partially, both governance and intellectual capital have no significant effect on financial performance or on the possibility of financial distress. However, when governance is interacted with the intellectual capital variable and moderation testing is carried out, it is known that the interaction variable produces a positive coefficient on financial performance and a negative coefficient on the possibility of financial distress. Meanwhile, the direct effect of intellectual capital on corporate governance is not significant. This proves that in this study intellectual capital acts as a pure moderating variable. The results of this study imply that in the absence of high intellectual capital, corporate governance is proven to be inefficient in improving its financial performance and unable to protect the company from the risk of experiencing financial difficulties. Structurally, manufacturing companies in Indonesia already have various main organs needed to carry out good corporate governance mechanisms, but in practice these organs are allegedly not functional in carrying out their duties and roles in managing the company's business, so that governance becomes ineffective in influencing performance company finance